The political economy of active labour market policy - RECWOWE; Bonoli, Giuliano (Edinburgh, 2010)
"Active labour market policies have developed significantly over the last two decades across OECD countries, with substantial cross-national differences in terms of both extent and overall orientation. The objective of this paper is to account for cross-national variation in this policy field. It starts by reviewing existing scholarship concerning political, institutional and ideational determinants of ALMPs. It then argues that ALMPs is too broad a category to be used analytically, and develops a typology of four different types of ALMPs: incentive reinforcement, employment assistance, occupation, and human capital investment. These are discussed and examined through ALMP expenditure profiles in selected countries. The paper uses this typology to analyse active labour market policy trajectories in six western European countries, and shows that the role of this instrument changes dramatically over time. It concludes that there is little regularity in the political determinants of ALMPs. In contrast, it finds important institutional and ideational effects, the latter in the most recent phase in particular."